The Principle of Legality in Corporate Criminal Liability for Environmental Crimes in Indonesia - S., Alief Sugiarto (Manunggal Halim Jaya, 2025)
This study aims to analyze the relevance of the principle of legality in corporate criminal liability for environmental crimes in Indonesia. The principle of legality, which is the main principle in criminal law, faces challenges when applied to corporations as legal entities. The existing legal framework does not fully accommodate the characteristics of corporations, thereby creating legal uncertainty in the handling of environmental crimes. This study uses a normative juridical method with a legislative approach and a conceptual approach. The data sources were obtained from a literature review of relevant laws, regulations, legal literature, and court decisions. The results of the study indicate that the application of the principle of legality to corporations still needs to be strengthened, either through the harmonization of regulations, the formulation of technical guidelines, or the strengthening of the capacity of law enforcement officials. This strategy is necessary to ensure the effectiveness of corporate criminal liability and fair protection of the environment.